Corroborating evidence: new clues and evidence; the Black Dahlia murder - Rasmussen, William T. (Sunstone Press, 2005)
Torso murders : New Castle, Pennsylvania; Youngstown and Cleveland, Ohio; and Haverstraw, New York -- The case against William Heirens -- Georgette Bauerdorf, Elizabeth Short (the Black Dahlia), Jeanne Axford French (the Red Lipstick murder) and other Los Angeles victims.